1992
DOI: 10.1007/bf00185915
|View full text |Cite
|
Sign up to set email alerts
|

Myosin isoform transitions during development of extra-ocular and masticatory muscles in the fetal rat

Abstract: The late fetal development of rat extra-ocular and masticatory muscles was examined by myosin immunohistochemistry. The pattern of slow and neonatal myosin isoform expression in primary and secondary myotubes in these muscles was generally similar to that seen by others in limb muscles. We observed a consistent difference between the Sprague-Dawley and Wistar rats in the degree of maturity reached by all muscles studied at a particular age. In both strains, extra-ocular muscles were also about one day in advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…Previous studies had shown that in many animal species retractor bulbi is a completely fast muscle (Sartore et al, 1987;Mascarello and Rowlerson, 1992): in porcine retractor bulbi (Fig.·1B) RT-PCR revealed the expression of all three fast MHC isoforms and SDS-PAGE showed two bands corresponding to MHC-2X and MHC-2B and an additional band corresponding to MHC-Eo or extraocular. The band corresponding to MHC-2A was undetectable due to the low amount of this isoform: some single fibres containing MHC-2A were, however, identified (not shown).…”
Section: Electrophoresis and Western Blotmentioning
confidence: 78%
“…Previous studies had shown that in many animal species retractor bulbi is a completely fast muscle (Sartore et al, 1987;Mascarello and Rowlerson, 1992): in porcine retractor bulbi (Fig.·1B) RT-PCR revealed the expression of all three fast MHC isoforms and SDS-PAGE showed two bands corresponding to MHC-2X and MHC-2B and an additional band corresponding to MHC-Eo or extraocular. The band corresponding to MHC-2A was undetectable due to the low amount of this isoform: some single fibres containing MHC-2A were, however, identified (not shown).…”
Section: Electrophoresis and Western Blotmentioning
confidence: 78%
“…Serial sections (10·m) were cut in a cryostat and stained according to the protocol described by with the following antibodies: monoclonal BF-F3, which is specific for MHC-2B in rat and in pig (Lefaucheur et al, 2002;Toniolo et al, 2004), polyclonal anti-MHC-Eo (Sartore et al, 1987) and polyclonal anti-MHC-Neo (Mascarello and Rowlerson, 1992). The procedures to assess the specificity of the reactions were described in Maccatrozzo et al (2004).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Immunohistochemical staining is conducted using an indirect immunoperoxidase method after incubation of tissue sections in MyHCspecific antibodies. The following MyHC-specific antibodies were used: anti-type I monoclonal (slow skeletal MyHC -Sigma Aldrich clone NOQ7), antifast monoclonal (fast skeletal IIA, IIB and IIX MyHC -Sigma Aldrich clone MY-32), anti-IIA monoclonal (fast IIA -American Type Culture Collection clone SC-71), anti-IIB (American Type Culture Collection clone BF-F3), antineonatal polyclonal [Scapolo et al, 1991], antitonic polyclonal [Mascarello and Rowlerson, 1992], anticardiac monoclonal (cardiac ·MHC -Sera Lab clone MAS-366 and BAG5; American Type Culture Collection Clone BA-G5), and anti-IIM polyclonal . Subsequent to staining serial sections with a panel of antibodies and a series of histochemical stains after various acid and alkali preincubations, biopsies are characterized for the proportions, size and types of fibers present.…”
Section: Histochemistry and Immunohistochemistry Of Tissue Sectionsmentioning
confidence: 99%